Anemia e fatores associados em crianças assistidas por creches públicas - Ribeiro, Eloiza Spinola [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Objective: To identify the prevalence of anemia and factors associated with this disease under attended by public nursery children, with a view to proposing clinical nursing protocol and organization of primary health care services to provide nutrition surveillance. Method: The authors conducted an epidemiological, cross-sectional study. The study sample was intentional and formed by 221 children between six months and six years of age, enrolled in three public kindergartens in the municipality of Guararapes (SP), located in the northwestern region of São Paulo. The sample of capillary blood (fingerstick) collected from each participating child was processed on laptop hemoglobinometer, considering anemia hemoglobin below 11g/dl. The overall nutritional status was assessed from indicators: height for age, weight for height and BMI for age expressed as Z-scores, using as reference the standard of the World Health Organization, 2006. Two nutritional classifications were adopted: advocated by Nutritional Surveillance System of the Ministry of Health for individual attention to the child and recommended by the World Health Organization for epidemiological studies. Socioeconomic and demographic data on the families maternal and paternal were collected through the individual records of children and by means of a questionnaire sent to parents. A descriptive analysis and cross-tabulations between anemia and the factors of interest, with significance evaluated by chi- square test.Results: The mean hemoglobin concentration was 10.8 g / dl (SD = 1.38). The prevalence of anemia was 51.1 %, 42.1 % showed the path to take shape and moderate 9.0 %. The frequency of children with short stature was 6.7%. According to the BMI index / age, 32.6 % of children had some situation involving overweight: risk of overweight (24 %), overweight (7.2%) and obesity (1.4%). You can check inverse linear association between child's age and anemia: ...

Objetivo: identificar a prevalência de anemia e fatores associados a esse agravo em crianças assistidas por creches públicas, com vistas a propor protocolo clínico de enfermagem e de organização dos serviços de atenção primária à saúde para ações de vigilância nutricional. Método: realizou-se um estudo epidemiológico, transversal. A amostra de estudo foi intencional e formada por 221 crianças entre seis meses e seis anos de idade, matriculadas em três creches públicas do município de Guararapes (SP), situado na região noroeste do Estado de São Paulo. A amostra do sangue capilar (punção digital) coletada de cada criança participante foi processada em hemoglobinômero portátil, considerando-se anemia valores de hemoglobina inferiores a 11g/dl. O estado nutricional global foi avaliado a partir dos indicadores: altura para idade, peso para alturae IMC para idade, expressos em escores-Z, utilizando-se como referência o padrão da Organização Mundial de Saúde-2006. Foram adotadas duas classificações nutricionais: a preconizada pelo Sistema de Vigilância Nutricional do Ministério da Saúde para a atenção individual à criança e a recomendada pela Organização Mundial de Saúde para estudos epidemiológicos. Dados socioeconômicos das famílias e demográficos maternos e paternos foram coletados através dos prontuários individuais das crianças e por meio de questionário enviado aos pais. Realizou-se análise descritiva e tabulações cruzadas entre presença de anemia e fatores de interesse, com significância avaliada pelo teste qui-quadrado. Resultados: a média de concentração de hemoglobina foi 10,8 g/dl (DP=1,38). A prevalência de anemia foi 51,1%; senda que 42,1% apresentaram a forma leve e 9,0% moderada. A frequência de crianças com baixa estatura foi 6,7%. Segundo o índice IMC/idade, 32,6% das crianças apresentavam alguma situação envolvendo excesso de peso: risco de sobrepeso ...
Keywords: Anemia em crianças; Creches; Crianças - Assistencia em instituições; Estudos transversais; Cuidados primários de saúde; Anemia in children